2003
DOI: 10.1111/j.1745-459x.2003.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computer‐generated Images and Conjoint Analysis to Investigate Sensory Expectations

Abstract: Consumers unfamiliar with passion‐fruit juice were presented with 24 computer generated package images on which six packaging factors (background color, picture, information, brand, language and shape) had been manipulated and asked to give scores for six expected sensory attributes (sweetness, pureness, sharpness, refreshing, freshness, naturalness) and liking. Significant effects were obtained for each attribute, with background color and information being the most important. Consumers varying in Need For Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 55 publications
2
96
0
3
Order By: Relevance
“…As I have mentioned above, studies on illusions show that sense perception is expectation-laden (see, e.g., Deliza et al 2003). Such studies suggest that sense perception does not simply give us direct access (unmediated by inference, whether conscious or otherwise) to the facts.…”
Section: Objections and Repliesmentioning
confidence: 96%
“…As I have mentioned above, studies on illusions show that sense perception is expectation-laden (see, e.g., Deliza et al 2003). Such studies suggest that sense perception does not simply give us direct access (unmediated by inference, whether conscious or otherwise) to the facts.…”
Section: Objections and Repliesmentioning
confidence: 96%
“…Among the qualitative methods is Focus group, which is defined as a way to interview in a carefully planned manner, to obtain individual opinions of a group of people on a particular area of interest. Because of the exploratory character, Focus group sessions have been fairly applied when little is known about the subject (Deliza et al, 2003), also allowing the identification of the relevant features of a particular product that affect consumers' choice; or discuss new product concepts and raise important attributes of the product packaging (van Kleef et al, 2005). Several studies have been reported using such as methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Several of them would be willing to pay more for products with reduced salt content compared to the conventional product counterparts. Deliza et al (2003) showed that consumers infer the flavor of the product from the label, revealing that many package attributes affected the perception and expectation regarding the product. It should be emphasized, however, that the results of several studies suggested that consumers are not willing to compromise taste for possible health benefits (Tuorila & Cardello, 2002;Verbeke, 2006).…”
mentioning
confidence: 99%
“…In fact, colour is one of the most potent features in the design of product packaging in the food industry (e.g., Deliza, MacFie, & Hedderley, 2003;Hutchings, 2003). According to Hine, consumers perceive packaging colour at three different, and, in practice, interrelated levels: the physiological, the cultural, and the associational.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been published over the years documenting the role that packaging colour plays in driving consumer expectations (e.g., Deliza et al, 2003;Marshall, Stuart, & Bell, 2006;Piqueras-Fiszman, Ares, & Varela, 2011). The reality is that people are affected by packaging, specifically by its colour, in ways that they do not necessarily understand at a conscious level (see Sacharow, 1970;Wheatley, 1973).…”
Section: Introductionmentioning
confidence: 99%